Konektivitas Pemikiran Politik Islam dengan NKRI Berdasarkan Pancasila (Membaca Pemikiran Munawir Sjadzali) - Hironimus Bandur (STIPAS St. Sirilus Ruteng, 2020)
One of Muslim figure, Munawir Sjadzali in many of his writings talked about Islam and state administration. This paper explains Sjadzali’s views on Islam and political/state administration historically and their relevance to the NKRI which is based on Pancasila, not based on a particular religion, not a secular state nor but a religious state. Academically, Sjadzali based on the condition of the internal Muslim factions: there was a traditionalistic-integralistic group, there was also a secularistic?partialist group. An exploration history of Sjadzali’s shows that tensions and differences of opinion about Islam and politics among Muslim communities have taken place since the time of the death of the Prophet Muhammad and continues to nowdays. Sjadzali in this paper ignores two extremes and follows one golden mit which is called a symbiotic view, towards Neo-modernism Islam. According to Sjadzali, Islam has a set of principles and ethical values for community and state life as can be found in the Quran, but still has flexibility in its implementation with due regard to the situation of the times and culture. The political system/state administration Islamic when compared to Pancasila, actually there are similarities in principles and enthusiasm.